Pengaruh Model Pembelajaran Thinking Aloud Pair Problem Solving Terhadap Hasil Belajar IPA Fisika Siswa - Mariyana, Rina; Ahzan, Sukainil; Sukroyanti, Baiq Azmi (IKIP Mataram, 2018)
[Title: The Effect of Thinking Aloud Pair Problem Solving Learning Model Toward Student Physics Science Learning Outcomes]. This study aims to determine the effect of learning model Thinking Aloud Pair Problem Solving on the results of science learning Physics Class VIII SMPN 6 Praya Timur. This research is a quasi-experimental research with Posttes -Only Control Design research design. The samples of this research are taken using Purposive Sampling technique with class VIIIc as the experiment class is 24 students and VIIId as the control class is 24 students. The instrument used in the form of test description in the form of 10 questions that are tailored to the learning indicators. The result of data analysis obtained using t-test at 5% significant level shows that the value of tcount> ttable (tcount = 0.634 & ttable = 0201) then Ha in receipt. so it can be concluded that the learning model Thinking Aloud Pair Problem Solving can affect the results of science learning Physics Student.